SINTESIS TURUNAN KITOSAN MELALUI REAKSI CANGKOK DAN TAUT SILANG DAN APLIKASINYA SEBAGAI MEMBRAN HEMODIALISIS - , Retno Ariadi Lusiana ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The main purpose of this research is to modify chitosan through substitution with active groups used for the formation of hydrogen bond with permeates which can increase the amount of carrier compounds in the membrane. In addition, substitution with an appropriate active group should be able to change to membrane surface charge so that adsorption on the surface can be reduced. Four strategies were used for this purpose: 1) grafting with chloroacetic acid as a compound having only one reactive group